MEMBANGUN JARINGAN SOSIAL DALAM PENERAPAN DAKWAH DI TENGAH MASYARAKAT - Abdul Asis Ibrahim; Dewi Asri Ulandari (Mudabbir: Jurnal Manajemen Dakwah, 2020)
Da'wah is an activity that functions as an appeal, invitation, to mankind to return to the right and good path according to religious teachings, and the religion that is blessed by Allah SWT is Islam, this is the basis that Islam is a religion of "rahmatan lil alamin" that is, a mercy for all of nature. In the implementation of effective and efficient dakwah activities, it requires a neat and strong social network, because social networks have links between individuals and individuals, individuals and groups, or groups and groups, so that the existence of this social network will have an effect on systematic da'wah work patterns. and structured to achieve the objectives of the da'wah itself